Skip to main content

Questions tagged [conjunctive-normal-form]

A formula is in conjunctive normal form (CNF) if it is a conjunction of clauses, where a clause is a disjunction of literals.

Filter by
Sorted by
Tagged with
-1 votes
1 answer
41 views

Find Conjunctive Normal Form of a compound proposition [duplicate]

I want to find CNF (Conjunctive Normal Formula) of the following proposition: $(¬p∨¬q∨¬r)→¬ ((a→¬b) ∨q)$ My attempt: If I use the result that $p→q ≡¬p ∨q$ then $(¬p∨¬q∨¬r)→¬ (¬a∨¬b ∨q)$. Again if I ...
Priya's user avatar
  • 4,570
-1 votes
1 answer
40 views

Given a formula how can we figure out if it is CNF or DNF

Can anyone please help me understand if the following formulas are DNF, CNF, both CNF and DNF, and neither CNF nor DNF? From my understanding, CNF is a conjunction of disjunction literals and DNF is a ...
Super Code's user avatar
1 vote
1 answer
58 views

I've found the minimal AND-OR expression for a function, but I can't find the minimal OR-AND function

I am given a function $f(W,X,Y,Z)$ that only outputs $1$ if exactly three inputs are $1$. The AND-OR function is easy enough to find: $$ W'X\,YZ + WX'YZ + WX\,Y'Z + WX\,YZ' $$ I think that function is ...
Daniel's user avatar
  • 71
0 votes
0 answers
43 views

Provide a clause set representation of a formula in CNF with a minimal number of clauses which is semantically equivalent to the KV map provided.

$KV$ map: So far I have tried brute forcing to generate a CNF formula, but that obviously doesn't give me the minimal CNF. I am left with $6$ sets with $4$ elements each and I can't simplify them. ...
Ömer Kural's user avatar
0 votes
0 answers
72 views

What is the Tseitin transformation of a single literal?

The wikipedia page for Tseitin transformation includes a nice example of the transform itself. In the example, it is implied that there is no need to create a fresh variable for a single literal (that ...
ampersander's user avatar
0 votes
1 answer
28 views

Is there any kind of distributive law for $c\cdot\max(a,b)$, allowing both signs of $c$?

Notation: For any two numbers $a$ and $b$, let the maximum be $a\sqcap b$, and let the minimum be $a\sqcup b$. (No, my symbols aren't upside-down. Compare this with floor notation; $\lfloor a\rfloor\...
mr_e_man's user avatar
  • 5,874
2 votes
1 answer
54 views

Is an idempotent logical expression considered to be in conjunctive normal form?

Is $$A \lor B \lor A$$ technically in conjunctive normal form? Or must we apply the idempotent law for it to be in CNF? $$A \lor B \lor A \equiv A \lor B$$?
justanotheruser's user avatar
0 votes
1 answer
339 views

Transform to CNF (conjunctive normal form)

I am trying to convert the following expression to CNF (conjunctive normal form): $\left(A\Rightarrow B\right)\Rightarrow\left(A\Rightarrow C\right)$ As my first steps I am removing the implications ...
Student17's user avatar
1 vote
2 answers
81 views

CNF form of the logical $atleast(b) x_{i,k}$

Suppose there exists the following logical expression: $$(\sum_{i=1}^I x_{(i,k)} \leq b) \implies (z_{(j,k)}=1) \quad \forall j \in J, k \in K \tag{1}$$ where all of variables, $x_{(i,k)}$ and $z_{(j,...
A.Omidi's user avatar
  • 149
-2 votes
2 answers
62 views

How to form a CNF of following formula [closed]

We got an exercise to make a CNF out of the following formula: $$G = ((A \vee \neg B \vee C) \wedge (C \vee D)) \vee ((A \vee \neg C) \wedge (B \wedge D))$$ I've tried to make an equivalent equation ...
Maxim Glazunov's user avatar
4 votes
1 answer
99 views

Is there a "standard" normal form for formulas in linear logic?

For propositional logic, for every formula, there is an equivalent formula in the CNF and DNF. These normal forms have the advantage of being representable in a "tabular" form rather than a &...
user1747134's user avatar
0 votes
1 answer
158 views

Resolution when CNF form has multiple conjoined disjunctive clauses

I've seen multiple examples of how resolution works when one has two disjunctive clauses with one having a negated literal present in the other clause. And when you resolve the two, you eliminate the ...
Apekshik Panigrahi's user avatar
0 votes
1 answer
65 views

Question about clausal form

The propositional logic textbook I'm working through explains how to convert a formula in conjunctive normal form to clausal form, for instance: ((p ∨ ¬p ∨ r) ∧ (¬p ∨ ¬q ∨ r)) ∧ ((p ∨ ¬p ∨ q) ∧ (¬r ∨ ¬...
Gerhardus Carinus's user avatar
0 votes
1 answer
39 views

Trouble with converting the negation of a formula to CNF

I'm trying to convert the negation of the following formula to CNF: (p → (q → r)) → ((p → q) → (p → r)) These are the steps I am following: ¬((p → (q → r)) → ((p → q) → (p → r))) ¬(¬(¬p ∨ (¬q ∨ r)) ∨ (...
Gerhardus Carinus's user avatar
0 votes
1 answer
93 views

CNF form of the logical $exactly(2) x_{i}$

Let's say, in order to linearize the product of the two binary variables the logical condition would be, z <=> (x and y), where x, y, and z are binary. The corresponding CNF form is as follows: \...
A.Omidi's user avatar
  • 149
0 votes
1 answer
124 views

Any proposition is equivalent to a formula in CNF.

A proposition is said to be in conjunctive normal form (CNF) if it is $\land_{i=1}^{k}\lor_{j=1}^{n} \psi_{ij}$ where each $\psi_{ij}$ is either an atom or is the negation of an atom. Show that any ...
kocaman's user avatar
1 vote
0 answers
42 views

How to define disjunctive normal form and conjunctive normal form?

The question is here: (1) Obtain the disjunctive normal form of $(p\to q)\to(q\to p)$ (2) Obtain the conjunctive normal form of $(p\to q)\to(q\to p)$ I obtain the form $\lnot q\lor p$. Is it a ...
Adi_Hsiao_0410's user avatar
1 vote
1 answer
432 views

How to convert this CNF to a DNF?

(((p ∨ q) ∧ (¬q ∨ ¬r)) ∧ (¬p ∨ r)) I know we can use a truth table, but I'm trying to convert by equivalences. It seems like it will blow up, but I may be doing this wrongly. Could someone let me know ...
coderperz's user avatar
3 votes
1 answer
113 views

Prove 20-3-SAT is NP-Complete

so I have this problem that I can't figure out. 20-3-SAT={All satusfiable 3-CNF formulas where each variable appears at most 20 times} I was able to prove it's in NP using verifier, but for NP-Hard ...
user3265447's user avatar
1 vote
1 answer
286 views

Duality in Disjunctive Normal Form and Conjunctive Normal Form

In my understanding, duality $s ^{*}$ of a compound proposition $s$ is obtained by replacing each $\vee$ to $\wedge$, each $\wedge$ to $\vee$, each $T$ to $F$, and each $F$ to $T$. I have been looking ...
Jiho Kim's user avatar
  • 143
0 votes
1 answer
52 views

At most $k$ contiguous $\mbox{true}$ values in a Boolean array using SAT

Given an integer $k > 0$ and a Boolean array $A$ of length $n$, find a simplified and efficient CNF formula to ensure that there is not more than $k$ contiguous $\mbox{true}$ values in this array. ...
juaninf's user avatar
  • 1,254
0 votes
1 answer
143 views

Is there a method to solve 3SAT problems using loss function?

Loss function seems to be used to solve optimization problems. I assumed that 3SAT problems can be treated as them. I would like to know whether there is a good loss function that is defined by ...
cozzie9806's user avatar
1 vote
1 answer
122 views

I'm studying boolean algebra in the discrete mathematics

problem Let $a_4a_3a_2a_1a_0$ be a 5- bits binary numbers (each $a_i=0$ or $1$). Write an expression in Boolean algebra that evaluates to $1$ when odd number of bits of the number is $1$ and $0$ ...
topst's user avatar
  • 159
0 votes
1 answer
233 views

Why doesn't Krom's method apply to solving the 3SAT in polynomial time?

In the paper "The Decision Problem for a Class of First-Order Formulas in Which all Disjunctions are Binary", Krom suggested a method to solve 2SAT problem. My understanding is this. Use ...
cozzie9806's user avatar
0 votes
0 answers
64 views

How to deduce the PDNF of ~A?

For my question, $A =\lnot P\land(Q \to R)$. After making the truth table, I managed to get the PDNF of it which is $$(\lnot p\land q\land r)\lor(\lnot p\land\lnot q\land r)\lor(\lnot p\land\lnot q\...
Yong Yung Fook's user avatar
1 vote
1 answer
159 views

Proposition is CNF and DNF

So I understand that CNF is the conjunction of one or more disjunctive clauses and that a DNF is a disjunction of one or more conjunctive clauses, however, I was wondering if there could be a case ...
55annoying ideas's user avatar
0 votes
1 answer
93 views

Finding the CNF of PL formula

I have this expression and I'm trying to find the CNF for it. (P ∨ (Q↔R))∧¬(Q→R) I have followed the steps of simplification until the distribution of "V". This is my current expression: (P ∨...
Igor9094's user avatar
0 votes
1 answer
97 views

CNF boolean formula satisfiable for a subset of $\{0,1\}^n$

For a set $S\subseteq\{0,1\}^n$, I want to make a CNF boolean formula $\phi$ such that for $ a=( x_1,...,x_n)$ we have $\phi(a)=1$ if and only if $a\in S$. I would also like to know what the size of ...
Jova's user avatar
  • 433
-2 votes
1 answer
453 views

Normal disjunctive and conjuctive form from a truth table

Let's say that we get a table with zeros and ones. We need to get it into disjunctive normal form or conjuctive normal form. We also have discrete variables $x_1,..,x_n$ that are either $1$ or $0$. ...
VLC's user avatar
  • 2,527
-1 votes
1 answer
1k views

How to convert a boolean function to CNF?

Consider the boolean function: $$f (x, y, z) = (x + \overline y) (y + \overline z) (z + \overline x)$$ I have converted it to DNF which is $xyz + \overline y \,\overline z \,\overline x$, but I have ...
CFI's user avatar
  • 11
0 votes
0 answers
76 views

Formalizing with Induction

In this thread here, it makes sense why there is exponential blow up because of the conversion. My question is how would we use induction to prove this? I've started, but I'm getting mixed up with the ...
UnevenMango's user avatar
-1 votes
1 answer
403 views

Checking tautology

Given a Boolean formula $\phi$ in CNF form, I'll check whether there exists a clause that can be falsified i.e. check for literals of the form $x \vee \neg x$. If there are not any such literals in a ...
Nikhil Ayyadevara's user avatar
0 votes
0 answers
123 views

Tseitin-Expansion for First-Order Logic

I want to transform an arbitrary formula of first-order logic into a CNF, or rather into a Skolem formula, whose matrix is in CNF. Standard procedure: First skolemize (the prenexed formula), then ...
un0wn's user avatar
  • 1
1 vote
1 answer
458 views

For CNF and DNF why do we look at the interpretations that make the formula false and true respectively?

Okay so I know how to obtain CNF and DNF from a truth table but I do not understand why. For example, for the formula $$P ⟺ Q$$ We are trying to convert the formula P ⟺ Q to an equivalent formula in ...
computerscienceisapain's user avatar
0 votes
0 answers
155 views

How do I expand this sigma/summation notation?

I don't know if it's correct to refer to this as summation notation since the operation is not addition so please correct me if that's inaccurate. How do I expand this notation? I believe it's for <...
LuxuryMode's user avatar
0 votes
1 answer
32 views

Find the CNF of the following formular

I am looking at the CNF of $((A \to B) \to (B \to A)) \to A$. For this I tried the following: $${\quad((A \to B ) \to (B \to A)) \to A\\ \equiv ((\neg A \vee B) \to (\neg B \vee A) \to A \\\equiv (\...
Frederick Manfred's user avatar
0 votes
1 answer
380 views

How do I re-write this propositional formula in conjunctive normal form (CNF)?

I'm struggling with this problem -- though it would seem simple enough. I think it's the parentheses that are getting me confused here. I need to convert (p→(q⋁r))⋁(s↔t) to conjunctive normal form (...
qscott86's user avatar
  • 103
1 vote
1 answer
44 views

Conjunctive Normal Form of a clause

Can the following clause be converted to conjunctive normal form? If so how? $$ (a \implies b) \implies (c \implies d) $$ I tried applying DeMorgans laws and am unable to get the result. $$ (a \...
Nick's user avatar
  • 1,079
1 vote
0 answers
174 views

Help with Resolution Refutation Problem

I'm trying to convert Solve a Resolution Refutation problem. The problem states: Knowledge Base is ∀𝑥𝑦 𝐹(𝑥, 𝑦). Prove using resolution-refutation that ∀𝑥𝑦 𝐹(𝑦, 𝑥). Note: β = F(y, x) This ...
Baiano42's user avatar
0 votes
1 answer
24 views

expanding disjunctive pairs of conjunctives using distributive law

I am having a bit of a brain malfunction. I am working through a functional programming class and I am trying to in parallel fake some knowledge of discrete mathematics. I am working through a simple ...
Mason Edmison's user avatar
2 votes
1 answer
236 views

Can clause normal form include true/false constants?

As Wikipedia puts it, ... the only propositional connectives a formula in CNF can contain are and, or, and not. The not operator can only be used as part of a literal, which means that it can only ...
rwallace's user avatar
  • 245
0 votes
1 answer
289 views

How to get CNF of propositional formula form DNF of its complement?

Explain how to read off a CNF for propositional formula directly from a DNF from its complement. I've managed to explain it in words, but can't write a rigorous proof of that. How to show this in ...
user avatar
0 votes
0 answers
148 views

Generalisation of DNF to CNF for DNF of m choose l clauses

Given two values $m$ and $l$, I can create corresponding DNF formula which is a disjunction of all $m \choose l$ combinations, where each number corresponds to a variable. Each combination is, in ...
sxt643's user avatar
  • 1
1 vote
1 answer
334 views

The Explanation on how to form CNF

I am currently reading Logic in Computer Science Modelling and Reasoning About Systems (by Michael Huth & Mark Ryan). They introduced a fairly easy way to form conjunctive normal form (CNF) of an ...
k2pctdn's user avatar
  • 39
0 votes
1 answer
189 views

HORN algorithm - clarity needed

I have been spending some time studying the HORN algorithm, but my textbook, as well as most posts online, are quite vague around the steps taken. These are the steps from my textbook: My questions: ...
Gerhardus Carinus's user avatar
0 votes
1 answer
672 views

How to introduce conjunctions into a conditional statements so as to get the CNF and DNF?

I have the following conditional statement: ((p → q) → p) → p Knowing that CNF is a conjunction of disjunctions (and that DNF is a disjunction of conjunctions), we will obviously have to introduce ...
why_did_i_do_this_course's user avatar
0 votes
1 answer
135 views

Converting propositional logic formula to CNF

I have been trying to do this all day but I am not getting anywhere with it, could anyone help me? My formula is r → (p ↔ ¬q) And I want to convert it into CNF ...
qwerty654321's user avatar
0 votes
0 answers
142 views

Dominant set of a Graph - Convert to Conjunctive Normal Form

I am supposed to convert this problem to a Satisfiability Problem in Conjunctive Normal Form, but I have no idea how. The Problem: Determine, if there exists any dominant set for a Graph $G$ ...
John's user avatar
  • 13
0 votes
1 answer
995 views

Explain into disjunctive normal form

Can anyone tell me how to Express the following formula into disjunctive normal form ⌐ (p V q) ↔ (p ^ q). I have done few steps but I need your help.
Ankit Singh's user avatar
0 votes
1 answer
83 views

Converting $3$-variable truth table to 3CNF

I have a truth table for length $3$ binary strings, say $110$ and $001$ map to $1$ and everything else to $0$. Is there an an algorithm to represent this table as a 3CNF which is satisfied only by $...
taurus's user avatar
  • 187

1
2 3 4 5